The fall of the house of Usher - Manning, Matthew K. (Edgar Allan Poe graphic novels., 2013)
A graphic novel adaptation of the classic Poe tale in which the narrator visits Roderick Usher, who is dying under the spell of a family curse, and witnesses the final destruction of the Usher family.